Roots and Wings: Indonesia´s way to improvements of women´s health care - Hans-Gerd Meerpohl (Majalah Obstetri dan Ginekologi, 2019)
Indonesia is the world’s fourth most populous nation and the largest economy in Southeast Asia. The World Bank recently classified Indonesia as an emerging middle-income country. Enormous gains have been made in poverty reduction, cutting the poverty rate to more than half since 1999, to 9.8% in 2018.(1) However, based on March 2017 data, approximately 20 % of the entire population remain vulnerable of falling into poverty, as their income hover marginally above the national poverty line.(2) Unique challenges for Indonesia´s health care system reflects the fact that approximately 250 million inhabitants from more than 300 ethnic groups spread over 17.000 islands. Indonesia has set itself an ambitious goal of establishing universal health care by 2019, a move commended by the United Nations as part of the 2030 Sustainable Development Goals.(SDGs)  Women´s health care, including women’s empowerment and gender equality, is concerned as an especially important issue because - on a global scale- it is one area in which performance has been seen by many to be slow. (3) While Indonesia has experienced greater success in its efforts to reduce the under five mortality rate (27 per 1.000 live births in 2015), efforts to tackle maternal mortality has been less effective as rates have continued to persist above 125 per 100.000 live births over the past decade (6) Having some of those facts in my mind I started my visit to Indonesia and to Surabaya in October 2018 with the desire to understand in the end the country, the people and their health system challenges a bit better.